Hubungan Antara Mendengarkan Musik dan Perubahan Mood - Dian Tri Andini; Fikri Khusaini; Safa Puja Arsila; Sri Mulyeni (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2026)
The study aims to measure how human emotional states are affected by music, both in increasing happiness and helping individuals manage sadness, musical characteristics such as tempo, tonality, and lyrics play an important role in shaping listeners' affective responses, where upbeat music with fast tempo and major tonality tends to promote positive moods, while melancholy music with slow tempo and minor tonality is more likely to evoke mood reflective or sad. This study used a pseudo-experimental method with a pre-test and post-test design on a group of psychology students of the National University of PASIM, with two songs as a stimulus: